Waveguide amplification of dye fluorescece in NLC - Shtykov, Nikolay M.; Palto, Serguei P.; Umanskii, Boris A.; Rybakov, Dmitry O.; Simdyankin, Ivan V. (Photonics Letters of Poland, 2018)
The amplification of spontaneous fluorescence in a planar layer of a nematic liquid crystal doped with a DCM dye is experimentally studied in a waveguide mode of light propagation. The optical pumping threshold of the superfluorescence is 0.65 MW/cm2. The gain value reaches 0.0014 μm-1 at a pumping intensity of 1.38 MW/cm2. Full Text: PDF References Liquid Crystal Microlasers, Eds. L. M. Blinov, R. Bartolino (Kerala India, Transworld Research Network 2010). DirectLink H. Kogelnik, C. V. Shank, "Coupled‐Wave Theory of Distributed Feedback Lasers", J. Appl. Phys. 43, 2327 (1972). CrossRef I. P. Il’chishin, E. A. Tihonov, V. G. Tishchenko, M. T. Shpak, "Generation of a tunable radiation by impurity cholesteric liquid crystals", JETP Lett. 32, 25 (1980). DirectLink A. Yariv, M. Nakamura, "Periodic structures for integrated optics", IEEE Quant. Electr. 13, 233 (1977). CrossRef N. M. Shtykov, M. I. Barnik, L. M. Blinov B. A. Umanskii, S, P. Palto, "Amplification of the emission of a liquid-crystal microlaser by means of a uniform liquid-crystal layer", JETP Lett. 85, 602 (2007). CrossRef